Anion Reactivity in Cation‐Disordered Rocksalt Cathode Materials: The Influence of Fluorine Substitution. Issue 35 (2nd August 2020) - Crafton, Matthew J.; Yue, Yuan; Huang, Tzu‐Yang; Tong, Wei; McCloskey, Bryan D.
Abstract: The demand for high energy‐density, mass‐producible cathode materials has spurred the exploration of new material structures and compositions. Lithium‐excess, cation‐disordered rocksalt (DRX) materials are a new class of transition metal oxides that display high capacity and environmental friendly composition. These materials achieve their high capacities partially through oxygen redox, which leads to oxygen loss and detrimental reactivity with the electrolyte. It has previously been shown that oxygen loss can be suppressed by partial substitution of the lattice oxygen for fluorine, but the explicit mechanism behind this effect remains unknown. In this work, differential electrochemical mass spectrometry (DEMS) and titration mass spectrometry are used to quantify the primary electrochemical reactions occurring during the first cycle in DRX materials. Comparing a DRX oxide and a DRX oxyfluoride, it is shown that fluorination limits oxygen redox and suppresses oxygen loss. Additionally, DEMS is coupled with fluoride‐scavenging to demonstrate that small amounts of fluorine dissolve from DRX oxyfluorides during the first cycle. Finally, these techniques are extended over the first several cycles, demonstrating that CO2 evolution persists and fluoride dissolution continues to a diminishing extent during the first few cycles. These findings motivate surface modifications to control interfacial reactivity and improve long‐term cycling. Abstract : Fluorine to the rescue. Fluorine substitution into cobalt‐free cation‐disordered rocksalt (DRX) cathode materials is quantitatively shown to shift the balance between transition metal redox and lattice oxygen redox, resulting in reduced oxygen loss. Quantifying interfacial reactivity in DRX materials points to potential strategies to extend cycle lifetimes.